2009
DOI: 10.1136/jmg.2009.067215
|View full text |Cite
|
Sign up to set email alerts
|

The very low penetrance of cystic fibrosis for the R117H mutation: a reappraisal for genetic counselling and newborn screening

Abstract: Background: Cystic fibrosis (CF) is caused by compound heterozygosity or homozygosity of CF transmembrane conductance regulator gene (CFTR) mutations. Phenotypic variability associated with certain mutations makes genetic counselling difficult, notably for R117H, whose disease phenotype varies from asymptomatic to classical CF. The high frequency of R117H observed in CF newborn screening has also introduced diagnostic dilemmas. The aim of this study was to evaluate the disease penetrance for R117H in order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
101
5
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(113 citation statements)
references
References 34 publications
5
101
5
2
Order By: Relevance
“…Like the previous French collaborative study, the frequency of carrier fetuses in our series (2.8%) was similar to the carrier frequency for frequent mutations found in the French general population (2.9%) (Thauvin-Robinet et al 2009). It may therefore be supposed that the decrease in functional CFTR amount caused by simple CF carriage is not sufficient to cause abnormal digestive signs suggestive of CF.…”
Section: Updated Frequency and Risk Of Cfsupporting
confidence: 84%
See 1 more Smart Citation
“…Like the previous French collaborative study, the frequency of carrier fetuses in our series (2.8%) was similar to the carrier frequency for frequent mutations found in the French general population (2.9%) (Thauvin-Robinet et al 2009). It may therefore be supposed that the decrease in functional CFTR amount caused by simple CF carriage is not sufficient to cause abnormal digestive signs suggestive of CF.…”
Section: Updated Frequency and Risk Of Cfsupporting
confidence: 84%
“…This difference could be due to a sample size effect but could also suggest an association between such null mutations, with absence of full-length protein, even misfolded, and a tissue-specific and temporal regulation of CFTR expression in the digestive tractus (McCarthy and Harris 2005). Identification of CFTR-RD mutations, mutations of unknown significance and questionable cases makes genetic counseling delicate As rarely reported (Abramowicz et al 2000), mild or CFTR-RD associated mutations might be found incidentally while searching for CF-causing defects, in particular when one CF mutation has been identified, as was the case in our study for the splicing T5 Eight fetuses were found with a genotype compatible with CFTR-RD, and 1 CF fetus with the mild T338I (p.Thr338Ile, c.1013C[T) CF mutation, thereby illustrating that fetal bowel anomalies not only reveal classical CF but also mild forms of the disease, as observed in newborn screening for CF (Narzi et al 2007;Roussey et al 2007;Thauvin-Robinet et al 2009). In such cases of a genotype compatible with CFTR-RD in the fetus, careful management and genetic counseling are of utmost importance: the parents should be reassured and fetal sampling for prenatal diagnosis is not mandatory.…”
Section: Measurement Of Af-de Activities May Still Be Of Value Beforementioning
confidence: 63%
“…There is limited data on the long-term outcomes, but it is clear from epidemiological studies that a significant number will have minimal or no phenotypic consequence [8,9]. We also know from case reports that a small number will develop significant CFTR related airway disease that has an impact on their well-being and potentially their survival [10].…”
Section: Introductionmentioning
confidence: 94%
“…While the R117H-T7 genotype is associated with milder forms of CF such as CBAVD, and most of the time even absence of symptoms, the R117H-T5 can be identified in patients having elevated sweat chloride and clinical cystic fibrosis, which in some cases is severe (Thauvin-Robinet et al, 2009). …”
Section: Complex Alleles and Multi-class Mutationsmentioning
confidence: 99%